Pulse oximetry screening for critical congenital heart disease in Tanzanian newborns: Diagnostic accuracy, sensitivity, and specificity in a low-resource healthcare setting. - Naizihijwa Gadi Majani; Pilly Chillo; Mkiwa Akida; Judith Lamosai; Deogratias Nkya; Stella Mongella; Zawadi Kalezi; Godwin Sharau; Vivienne Mlawi; Peter Kisenge; Mohamed Janabi; Diederick Grobbee; et al. (PLOS Global Public Health)
Early detection of Critical Congenital Heart Disease (CCHD) is crucial for reducing infant mortality. Pulse oximetry (POX) is widely utilised for screening CCHD in high-resource settings; however, its diagnostic accuracy in low-resource environments, such as sub-Saharan Africa, remains under-researched. This study aimed to assess the diagnostic accuracy of POX in screening Tanzanian newborns for CCHD. This prospective cohort study was conducted in two hospitals in Dar es Salaam, Tanzania. We used pre- and post-ductal saturation (SpO2) readings prior to discharge. A positive screen was defined as SpO2 < 90%; two pre- and post-ductal SpO2 readings <95%; and/or a pre- or post-ductal difference that exceeded 3%. All newborns with positive screening tests underwent echocardiography, while those with negative tests were followed for six months. The primary outcome was POX diagnostic accuracy. The study adhered to STARD guidelines for reporting diagnostic accuracy studies. Between October 2020 and June 2023, 10,630 newborns were screened. The majority (5,721; 54.0%) were male, resulting in a male-to-female ratio of 1.2. The median birth weight was 3.0 (IQR: 2.6-4.4) kg. A total of 51 (0.5%) newborns tested positive on POX, of which 18 (35.3%) had congenital heart disease (CHD), and 15 (83.3%) were classified as critical, leading to a CCHD prevalence of 1.41 per 1,000 live births (95% CI: 0.70-2.13), which increased to a cumulative prevalence of 3.27 per 1,000 live births (95% CI: 2.29-4.67) at six months. With a follow-up rate of 86.7% (9,170/10,574), POX demonstrated a sensitivity of 50.0% (95% CI: 32.1-67.9), a specificity of 99.5% (95% CI: 99.4-99.7), a false-positive rate of 0.4%, and an overall accuracy of 99.5% (95% CI: 99.2-99.5). Screenings conducted between 48 and 72 hours exhibited the highest diagnostic performance, AUC 0.79 (95% CI: 0.64-0.93), with a significant odds ratio (OR) of 5.31 (95% CI: 2.45-11.49, p = 0.00001). Newborns with a birth weight <2.5 kg were less likely to have CCHD detected by POX, OR 0.403 (95% CI: 0.19-0.87, p = 0.021). POX demonstrated lower sensitivity but higher specificity and diagnostic accuracy after 48 hours. The timing of screening and birth weight affected its accuracy, indicating a need for protocol adjustment.